2008
DOI: 10.1016/j.exer.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C epsilon activates lens mitochondrial cytochrome c oxidase subunit IV during hypoxia

Abstract: Protein Kinase C (PKC) isoforms have been identified as major cellular signaling proteins that act directly in response to oxidation conditions. In retina and lens two isoforms of PKC respond to changes in oxidative stress, PKCγ and PKCε, while only PKCε is found in heart. In heart the PKCε acts on connexin 43 to protect from hypoxia. The presence of both isoforms in the lens led to this study to determine if lens PKCε had unique targets. Both lens epithelial cells in culture and whole mouse lens were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…6A). Considering that hypoxia is the natural state of the lens 13 and our previous data that PKCε is activated in the fresh lens, 50 we confirmed the activation of PKCε by detecting phosphorylated PKCε on Ser-729 in the whole lens lysates (Figs. 6B, 6C).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…6A). Considering that hypoxia is the natural state of the lens 13 and our previous data that PKCε is activated in the fresh lens, 50 we confirmed the activation of PKCε by detecting phosphorylated PKCε on Ser-729 in the whole lens lysates (Figs. 6B, 6C).…”
Section: Resultssupporting
confidence: 83%
“…Previously, we demonstrated that PKCε is a prerequisite for hypoxia-induced activation of the CytCOxIV. 50 The second possibility may result from an effect of PKCε on Cx43 which is absent in PKCε-KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CcO is a large transmembrane protein complex located on the inner mitochondrial [14]. Previous studies found that the protein kinase C could protect the lens from mitochondria damage under hypoxia through the activation of CcO enzyme activity [25]. In order to further clarify the mechanisms by which the PI3K-AKT pathway inhibits apoptosis, the activity of CcO was evaluated in cultured cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PKCs play important roles in lens development such as protection against hypoxia by PKCε of mitochondrial c oxidase IV subunits [4]. Inhibition of PKC, and hence phosphorylation of proteins involved in vital cellular functions, elicits apoptosis [5,6].…”
Section: Introductionmentioning
confidence: 99%